Cofinitely Generalized Lifting Module - Khalid, Wasan; Wadi, Adnan S (Al-Nahrain Journal of Science, 2019)
Let R be an associative ring with identity, and let M be a unitary left R-module. The main purpose of this paper is to introduce and study properties of class of modules including lifting module. We use the Radical submodule to introduce this class of modules. We start by defining a generalized lifting module as a generalization of lifting module, then we give another generalization of generalized lifting module we called it cofinitely generalized lifting module. Thus, we give characterization and prove some properties of this type of modules.